Strategisnya manajemen insani dalam penyediaan guru yang berkualitas - David Livingstone Araro; Herry Sumual; Fientje J.A. Oentoe; Jeffry Sony Junus Lengkong; Viktory Nicodemus Joufree Rotty (International Journal on Integrated Education, 2022)
The educational goals to be achieved include all aspects, both faith, personality, intelligence, and skills. Education seeks to create a superior personality marked by progress in all areas of life, whether spiritual, personality, intelligence, or skills, all of which will benefit students, the environment in which they interact, and also for the progress of the nation and state.This research was conducted using a qualitative descriptive approach. Sugiyono explained the characteristics of qualitative research methods as follows: "Qualitative research methods are research methods based on the philosophy of postpositivism, used to examine the condition of natural objects (as opposed to experiments), where the researcher is the key instrument, the sampling of data sources is carried out purposively. and snowball, data collection techniques with triangulation (combined), and inductive/qualitative data analysis, and qualitative research results emphasize meaning rather than generalization”. The results show that SGS has made plans but still needs improvement. The planning process for all human management activities which include teacher procurement, teacher development.